New quaterphenyls laterally substituted by methyl group and their influence on the self-assembling behaviour of ferroelectric bicomponent mixtures. Issue 6 (3rd May 2022) - Tykarska, Marzena; Kurp, Katarzyna; Zieja, Paulina; Herman, Jakub; Stulov, Sergei; Bubnov, Alexej
ABSTRACT: Design of new functional binary mixtures possessing the self-assembling behaviour remains a highlighted task in order to tune the resulting properties of soft materials according to specific application demands. Three new chiral compounds with a quaterphenyl core substituted by the methyl group in different positions and having different linkage groups between the chiral chain and the rigid core were synthesised and used as smart dopants to the basic compound possessing a highly tilted orthoconic ferroelectric smectic phase. The main aim is to establish the effect of the miscibility on the basic parameters of the resulting binary mixtures, specifically on the mesomorphic behaviour, values of the spontaneous polarisation, tilt angle, helical pitch length and dielectric behaviour. As the quaterphenyl dopants differ between each other in the linkage group placed between the chiral chain and the rigid core, these compounds influence physical parameters of the resultant mixtures in a different way. A small amount of quaterphenyl dopants does not considerably decrease the tilt angle, but in the case of the -O- atom presence, it results in a visible decrease of the spontaneous polarisation and increase of the helical pitch length. However, in the case of the -COO- group presence, it increases spontaneous polarisation and decreases the helical pitch (<200 nm). Graphical abstract: uf0001